Effect of temperature on the growth, feeding performance, gonadal development, and nutritive compositions in the muscle of fry stream groupers, Acrossocheilus fasciatus - Bo Zhao; Wei Shi; Yongyao Guo; Ye Chen; Handong Wang; Jinghong He; Zhangjie Chu (Journal of the World Aquaculture Society, 2024)
Abstract To determine the optimal temperature in rearing of fry stream groupers, Acrossocheilus fasciatus, a total of 540 fry fish with an initial body weight of (0.57 ± 0.16) g, and body length of (4.08 ± 0.40) cm were randomly distributed to 18 15‐L tanks and reared at six different temperatures (12, 16, 20, 24, 26, and 28°C) for a period of 60 days. Fish were hand‐fed to satiation under all six different temperature treatments. At the end of the experiment, almost all the growth, feeding, and gonadal development parameters were higher in the 26°C group than in the rest of the groups. As temperature increased from 12 to 26°C, the specific growth rate and feeding efficiency of fry significantly increased (p < 0.05). When temperature reached 28°C, these parameters were significantly lower than in the 26°C group (p < 0.05). The histological structure of the gonads showed that in the 26°C group, a large number of sperm cells resided in the testis in a free condition, and many yolk granules aggregated together and formed plates in the ovary. This histological information indicated that the gonadal maturity of fish in the 26°C group was higher than that of the other groups. Thus showing a turning point of growth, feeding, and gonadal development in the 26°C group. In relation to the nutritive compositions of muscle tissue, fish reared at 16°C exhibited the highest content of amino acids and fatty acids. These parameters significantly (p < 0.05) decreased as the temperature increased from 16 to 28°C. The proportion of essential amino acids (EAA/NEAA) and unsaturation of fatty acids (∑UFA/FA) did not show significant temperature influence (p > 0.05). In conclusion, increases in temperature significantly improved the growth rate, feeding performance, and gonadal development rate of fry A. fasciatus. Regression analysis based on growth and feeding performance showed that the optimal temperature of rearing fry A. fasciatus was 23.81–26.57°C.